2019
DOI: 10.3390/geosciences9070309
|View full text |Cite
|
Sign up to set email alerts
|

Recent Geomorphological Evolution and 3D Numerical Modelling of Soft Clastic Rock Cliffs in the Mid-Western Adriatic Sea (Abruzzo, Italy)

Abstract: Geomorphological evolution, erosion and retreat processes that affect the rocky coasts of the mid-western Adriatic Sea (Abruzzo, Central Italy) are the subject of this research. This coastal sector, one of the few examples of clastic soft rock coasts in the Mediterranean Sea, is characterized by active, inactive and paleo cliffs, as well as coastal slopes, composed of the clayey-sandy-arenaceous-conglomeratic marine sequence (Early-Middle Pleistocene) covered by continental deposits (Late Pleistocene-Holocene)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 34 publications
0
9
0
3
Order By: Relevance
“…LIDAR (Light detection and ranging) surveys (e.g., Roering et al, ), digital photogrammetry (e.g ., Liu et al, ; Romeo et al, ), and satellite surveys (e.g., Wang et al, ) are being used to create digital elevation models (DEMs) to study landslide events. Pre‐ and post‐event DEMS can be compared to obtain three‐dimensional estimates of volumetric change (e.g., Bossi et al, ; Calista et al, ; Fanos & Pradhan, ; Riquelme et al, ). As methods improve and additional pre‐ and post‐event DEMs are collected for more regions, there will be a reduced need to use landslide area measures to estimate volume measures.…”
Section: Future Directionsmentioning
confidence: 99%
“…LIDAR (Light detection and ranging) surveys (e.g., Roering et al, ), digital photogrammetry (e.g ., Liu et al, ; Romeo et al, ), and satellite surveys (e.g., Wang et al, ) are being used to create digital elevation models (DEMs) to study landslide events. Pre‐ and post‐event DEMS can be compared to obtain three‐dimensional estimates of volumetric change (e.g., Bossi et al, ; Calista et al, ; Fanos & Pradhan, ; Riquelme et al, ). As methods improve and additional pre‐ and post‐event DEMs are collected for more regions, there will be a reduced need to use landslide area measures to estimate volume measures.…”
Section: Future Directionsmentioning
confidence: 99%
“…As a consequence, the bedrock is now largely covered by near-surface clay-silt-sand-gravel Late Pleistocene-Holocene continental deposits (i.e. slope and landslide deposits, and fluvial and colluvial deposits; Calista et al, 2016;Calista et al, 2019;Carabella et al, 2020;Miccadei et al, 2012;Piacentini et al, 2015;Piacentini et al, 2018).…”
Section: Study Areamentioning
confidence: 99%
“…The obtained results allow us to put forward a hypothesis regarding the origins of the displacements. We presented a similar work in Reference [6], in which a landslide assessment was performed based on detailed topographic, geological, and geomorphological data and numerical modelling. However, researchers have shown that the method has a certain limitation; i.e., it can only be used on rocky shores.…”
Section: Introductionmentioning
confidence: 99%